The LOCTI and its importance in national development. A reflection (Gestión y Gerencia, 2026)
This reflection stems from a review and concern regarding the current situation of the actors comprising the National System of Science, Technology, and Innovation (SNCTI) concerning the application of the Organic Law of Science, Technology, and Innovation (LOCTI). It highlights Article 110 of the Constitution of the Bolivarian Republic of Venezuela (CRBV), as well as the application, repeal, and legislation of regulations and laws that, far from fulfilling the letter of Article 110, have become a form of coercive control, confiscatory leading to the closure of companies, their departure from the country, and disinvestment in Science, Technology, and Innovation (STI). Recommendations are proposed, emphasizing the urgent need to revitalize and reactivate the 2005 LOCTI, although, given the advances in global STI, some of its articles will require updating.
Keywords: SNCTI Actors; Investment in STI; LOCTI; SNCTI